Variable expression of a yeast-phase-specific gene in Histoplasma capsulatum strains differing in thermotolerance and virulence. - Keath, E J (1989)
By means of differential hybridization techniques, several yeast-phase-specific DNA sequences were identified in the dimorphic pathogenic fungus Histoplasma capsulatum. A 1.85-kilobase (kb) HindIII fragment from one genomic clone, yps-3, hybridized to at least three distinct yeast poly(A)+ RNAs of 1.3, 1.05, and 0.95 kb from the virulent strain G217B. These mRNAs were not detected in mycelia. When mycelia from G217B were induced to become yeast by transfer from 25 to 37 degrees C, a process requiring approximately 9 days, expression of yps-3 was detected within 24 h, although not in the initial 2 h following the temperature shift. In contrast, a low-virulence strain (Downs) which completes the transition in approximately 2 weeks failed to express the yps-3 gene during phase transitions. A third isolate, G186B, intermediate in its virulence properties and in the time required for the transition (11 days), expressed a single 1.25-kb mRNA but only at low levels in the yeast phase and only after 3 days following the 25-to-37 degrees C temperature shift. Although yps-3 expression does not appear to be essential for the transformation to the yeast phase, it may facilitate the early adaptive processes which permit the mycelium-to-yeast transition and survival of the yeast phase of H. capsulatum at elevated host temperatures. The phase-specific yps-3 nuclear gene is carried on highly polymorphic restriction fragments in all three strains, suggesting that this probe may provide a sensitive diagnostic tool for the classification of H. capsulatum isolates.